Modular integrated construction as a development strategy for post-COVID urban sustainability: the case of Hong Kong - Jia, Andrea Yunyan; Zhang, Yi; Shen, Jianfu (Frontiers in Sustainable Cities, 2025)
The UN Sustainable Development Goals (SDG) suggest a broader concept of health as the focus of development, i.e., economic growth to take into account of the health and wellbeing of a diversity of people included by age, gender, ability, ethnicity, economic status, region, and generation. With this understanding, a city’s development strategy should aim for win-win solutions for the broadest inclusion of people. The global pandemic has caused world economic recession and rising geopolitical tensions, but also the opportunity of digitalization and economic restructuring for more sustainable solutions. This study aims to explore sustainability solutions for the Hong Kong government under this situation, with particular reference to strategic choices related to construction. The Hong Kong government initiated the modular integrated construction (MiC) project delivery model, embedded in a cross-border supply chain, as a major strategy for industrialisation of construction, enabled by an updated institutional infrastructure and growing digital capabilities. On this basis, MiC will gain more market share in construction project businesses, necessitating closer regional collaboration. The MiC model is set to create a pathway towards participation in the carbon market and a gateway connecting green construction project activities with the eligibility for green fund.